Analysis of the epidemiological profile of maternal syphilis in the municipality of Palmas, Tocantins, from 2017 to 2021 (Research, Society and Development, 2022)
The syphilis epidemiological surveillance model is based on the compulsory notification of public and private health services throughout the national territory, and this information is registered in the Information System and Notifiable Diseases (SINAN). Thus, the objective of this study was to describe the epidemiological and statistical coefficients of reported cases of maternal syphilis in the municipality of Palmas, Tocantins, during the years 2017 to 2021. As a methodology, a cross-sectional study was carried out with analysis of time series for the period from 2017 to 2021, using data from Sinan. The results showed that during the study period (2017 to 2021) 749 cases of maternal syphilis were reported. The modal class of this variable corresponds to the age group from 20 to 29 years old, followed by the group from 15 to 19 years old, with a predominance of the South region of Palmas-TO. The most prevalent race was brown 493 (65.8%), followed by yellow 101 (13.5%), with complete high school n=209 (27.9%), in the latent form with n=490 (65.4%), followed by the primary form n=140 (18.7%). The most used treatment regimen was Penicillin G benzanthine 7,200,000 IU, with n=593 (79.2%) and Penicillin G benzanthine 2,400,000 IU, with n= 18 (2.4%). The reactive treponemal test was the most prevalent, with n=536 (71.6%). Although the diagnosis and treatment of syphilis is offered to all pregnant women free of charge, fully available through the Unified Health System (SUS), this condition is still a major challenge for reducing cases.